2005
DOI: 10.1097/01.smj.0000145283.69631.fc
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Prepregnant Body Mass Index and Weight Gain Related to Low Birth Weight in South Carolina

Abstract: Appropriate maternal BMI at conception followed by adequate weight gain during pregnancy may have a substantial influence on reducing the number of low birth weight deliveries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 7 publications
3
19
0
1
Order By: Relevance
“…This result was similar to the findings of several studies which demonstrated that maternal weight gain during pregnancy was an important risk factor for LBW infants [10,17]. The risk of LBW was significantly lower in mothers who had sufficient weight gain during pregnancy compared with mothers who did not have adequate weight gain [28][29][30].…”
Section: Discussionsupporting
confidence: 91%
“…This result was similar to the findings of several studies which demonstrated that maternal weight gain during pregnancy was an important risk factor for LBW infants [10,17]. The risk of LBW was significantly lower in mothers who had sufficient weight gain during pregnancy compared with mothers who did not have adequate weight gain [28][29][30].…”
Section: Discussionsupporting
confidence: 91%
“…Classification cutoffs for pre-gestational nutritional status were established based on data from the Metropolitan Life Insurance Company, which distinguished low-weight and overweight values from the range of normality-approximately 90% and 120%, respectively, of the ideal weight-for-height reference data (26). To determine the recommended weight-gain ranges during pregnancy, the IOM used data from the 1980 national survey of U.S. births of pregnancies from 39 to 41 weeks' gestation and birth weight between 3-4 kg as an operational definition of favorable obstetric results (6,18,(29)(30)(31).…”
Section: Historic Evolution Of Methodsmentioning
confidence: 99%
“…The defining values for LBW are still contested by authors, but lie somewhere in the region of 2500-2999g. 27,28 It has therefore become clear over the past decade that there is a need to review the objectives and the indicators for anthropometric assessment of pregnant women, especially the initial nutritional diagnosis using pre-gestational BMI. 29 The results of this study provide further evidence of the diffe- Helms et al 36 have explored the risks that inappropriate weight gain might bring for obstetric outcomes, pointing out that pregnant women whose weight gain was inadequate presented higher chances (OR=1.78; RI95% 1.7-1.86) of having LBW babies than those whose weight gain was adequate or excessive.…”
Section: Tabelamentioning
confidence: 99%
“…[37][38][39] Hulsey et al 40 found that lower than adequate maternal weight gain entails a greater likelihood of very low birth weight and moderate low birth weight, when compared to women with adequate weight gain. According to the ranges proposed by the IOM (OR=1.4 and 1.9, respectively).…”
Section: Tabelamentioning
confidence: 99%